Modeling and simulation of faulty induction motor in dq reference frame using matlab/simulink with matlab/guide for educational purpose - OYMAN SERTELLER, NECİBE FÜSUN; TOPUZ, VEDAT (My University, 2023)
Owing to their robust structure, induction motors are preferred to be used under difficult working conditions. Therefore, various faults may occur in the motor due to unexpected forces during the operations. Obtaining the data through experimental methods by physically creating faults in the induction motors, and analyzing their behavior is not efficient in terms of cost and time for educational purposes. Considering the above negative situation, in this paper, mathematical models have been developed in the dq0 stationary reference frame expressing three-phase stator windings short-circuit fault and broken rotor bar fault in induction motors. The proposed models are faster as compared to the other analytical models in terms of computation due to the rotor position independence of the inductance matrix. The faulty induction motor mathematical models have been implemented in the MATLAB/SIMULINK software environment with detailed explanations of each faulty model\"s subsystem. As a visual laboratory that can be used as an educational tool for the analysis of a three-phase faulty induction motor, a graphical user interface application has been developed in MATLAB/GUIDE, which allows users to simulate models from a single interface. As a case study, the behaviors of faulty induction motors in transient and steady states have been simulated in different severity scenarios of the faults. The park vector method has been used as a fault diagnosis approach to investigate fault types and the fault severity effects on the park vector pattern in each fault scenario. In addition, to observe the success of the developed Simulink toolboxes, they were used at Marmara University through courses in electrical machinery and evaluated by the graduated students at the end of the semester.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Induction Motor; dq Reference Frame; Stator Fault; Rotor Fault; Park Vector; MATLAB/SIMULINK; MATLAB/GUIDE; MONITORING TECHNIQUES; TRANSIENT ANALYSIS; STATOR FAULT; ROTOR-BAR; MACHINES